Non‐synchronous generation impact on power systems coherency. Issue 10 (1st July 2016) - Chamorro, Harold R.; Ordonez, Camilo A.; Peng, Jimmy C.; Ghandhari, Mehrdad
Abstract : The increasing integration of renewables into the grid based on power electronics converters interfaces is affecting the power systems dynamics, requiring effective monitoring and visualisation to provide appropriate assessment during extreme events. The coherent group identification in power systems is of importance for dynamic studies and transmission capability improvement. This study analyses the coherency based on the mode shapes, the application of the Koopman mode analysis (KMA) and a Prony analysis (PA) on‐line variation for the identification of coherent groups in power systems. KMA and PA use the voltage angle measurements obtained from simulation. The clustering of the coherent groups are evaluated in two test systems. The coherency methods are also evaluated taking into account the impact of a large gradual scale inclusion of non‐synchronous generation under different penetration level cases. From the comparison and visualisation of the different methods it is possible to observe the impact of the large inclusion of non‐synchronous generation on the coherency.